Profiling interactions of vaborbactam with metallo-β-lactamases. Issue 15 (1st August 2019) - Langley, Gareth W.; Cain, Ricky; Tyrrell, Jonathan M.; Hinchliffe, Philip; Calvopiña, Karina; Tooke, Catherine L.; Widlake, Emma; Dowson, Christopher G.; Spencer, James; Walsh, Timothy R.; Schofield, Christopher J.; Brem, Jürgen
Graphical abstract: Abstract: β-Lactams are the most successful antibacterials, yet their use is threatened by resistance, importantly as caused by β-lactamases. β-Lactamases fall into two mechanistic groups: the serine β-lactamases that utilise a covalent acyl-enzyme mechanism and the metallo β-lactamases that utilise a zinc-bound water nucleophile. Achieving simultaneous inhibition of both β-lactamase classes remains a challenge in the field. Vaborbactam is a boronate-based inhibitor that reacts with serine-β-lactamases to form covalent complexes that mimic tetrahedral intermediates in catalysis. Vaborbactam has recently been approved for clinical use in combination with the carbapenem meropenem. Here we show that vaborbactam moderately inhibits metallo-β-lactamases from all 3 subclasses (B1, B2 and B3), with a potency of around 20–100 fold below that by which it inhibits its current clinical targets, the Class A serine β-lactamases. This result contrasts with recent investigations of bicyclic boronate inhibitors, which potently inhibit subclass B1 MBLs but which presently lack activity against B2 and B3 enzymes. These findings indicate that cyclic boronate scaffolds have the potential to inhibit the full range of β-lactamases and justify further work on the development of boronates as broad-spectrum β-lactamase inhibitors.